Occult tinea pedis in an Israeli population and predisposing factors for the acquisition of the disease. (16th April 2014) - Sakka, Nicole; Shemer, Avner; Barzilai, Aviv; Farhi, Renata; Daniel, Ralph
Abstract Background Tinea pedis is a commonly encountered dermatophytic infection with a clinical prevalence of 15–25%. Limited studies have evaluated the prevalence of occult tinea pedis. Objectives The aims of this study were to evaluate the prevalence of occult tinea pedis in asymptomatic subjects with feet that appeared healthy and to identify possible related risk factors. Methods A prospective study of 221 asymptomatic subjects with apparently normal feet was conducted. All subjects completed a questionnaire covering anamnestic details (personal and family histories of tinea pedis, preferred footwear) and were examined for foot odor and the clinical presence of tinea pedis and onychomycosis. Samples were taken from the foot for direct microscopic examination and culture. Results Among the 221 patients, 31 (14.0%) were positive for occult tinea pedis. Positive cultures from both the anterior and posterior aspects of the foot were obtained in 22 patients. The most common pathogen isolated was Trichophyton rubrum. Strong correlations emerged between occult tinea pedis and characteristics such as male gender, foot odor, previous personal and family histories of tinea pedis, and clinical and mycological evidence of onychomycosis. No significant associations were found between occult tinea pedis and age or preferred footwear. Conclusions The prevalence of occult tinea pedis is similar to that of clinical tinea pedis. This may imply that patients with subclinical infection carry a risk for transmitting disease similar to that of clinical carriers. This is of great importance in the prevention and management of the disease as high‐risk asymptomatic carriers can be identified.